Vase life extension of gerbera using different preservative vase solutions (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was conducted at the Postharvest Laboratory, Horticulture Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, during January-February 2024 to evaluate different preservative solutions for vase life extension of gerbera. Two varieties of gerbera were collected from commercial growers in Jhikargacha, Jashore. The experiment was laid out in two-factorial completely randomized design included Factor A:  flower variety  (V1- Sangria Red and V2- Olivia White) and Factor B: preservative vase solutions ( T0: control-Tap water, T1: 3% sucrose solution, T2: 250 ppm citric acid solution, T3: 250 ppm AgNO3 solution, T4: 2% lemon Juice, T5: 150 ppm citric Acid + 150 ppm AgNO3,  T6: 2% sucrose + 150 ppm citric acid, T7: 2% sucrose + 150 ppm AgNO3, T8: 1% sucrose + 100 ppm AgNO3 + 1% lemon juice and T9: 1% sucrose + 100 ppm AgNO3+ 100 ppm citric acid). Data were recorded were flower diameter, freshness, petal discoloration, solution uptake, pathogen attack and vase life. Results showed significant varietal differences; V2 exhibited longer vase life (12.7 days) than V1 (11.6 days). The longest vase life (13.5 days) was recorded in V2T2, while the shortest (10.3 days) of the same was found in V2T5. Findings suggest suitable preservative solutions can reduce postharvest losses and improve marketability under ambient conditions.Bangladesh J. Nuclear Agric, 39(2): 35-48, 2025